Pengembangan Sistem Informasi Geografis Cagar Budaya di Malang Raya Berbasis Webgis, 3D, dan Gamifikasi - Machrus Alawi; Fatwa Ramdani; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Preserve culture is a cultural heritage that is material in the form of cultural heritage, the cultural heritage building, the structure of cultural heritage, the cultural heritage site, and the cultural heritage on the ground or in water that needs to be preserved the existence of it because it has significant value for history, religion, education, science and culture through the process of setting that have criteria in the form of unity or group who was at least less than fifty years, or on behalf of the style typical and representative of the style of at least fifty years. There are problems about the people's lack of awareness and knowledge of the importance of cultural heritage and values of culture. And the factor of the nature and theft that would eliminate the Preserve culture. One of the preservation that can be set is to make Geographic Information System (GIS). In this case as an object research is the temple and statue in Malang Raya (the city of Malang, Batu, and the District of Malang). Make GIS cultural heritage just not enough because the system the information will only display the location and information about the history of the site. Research is also using the method of 3D visual and gamification. Where's temple site and statue at each location will be used as a 3D model and history and information from each temple site and statue will be made in the game a quiz that will support GIS which was built. As a result of this research is a website based on a GIS capable of mapping the location of cultural heritage (the temple and statue) in Malang Raya, visualization of 3D models of every temple and statue, the game a quiz about the history of the temple and statue.